# P2 Trig! ARGHHHWatch

This discussion is closed.
14 years ago
#21
(Original post by lgs98jonee)
hang on...ur idea of using cosP -cosQ=0 works on the question doesnt it? I used that method and got all the solutions...or am i missing sumthing here
well i thought so, but Squishy seems to think otherwise?
0
14 years ago
#22
(Original post by lgs98jonee)
hang on...ur idea of using cosP -cosQ=0 works on the question doesnt it? I used that method and got all the solutions...or am i missing sumthing here
works for me
0
14 years ago
#23
(Original post by kikzen)
bleh.. solve it then
0
14 years ago
#24
(Original post by Squishy)
oh lol heh, great sig tho
0
14 years ago
#25
(Original post by Katie Heskins)
Theres nothing wrong with assuming the result you're trying to prove providing you don't do anything invalid, therefore lgs98jonee's is fine because he hasn't made any errors which may have lead to an invalid proof.
This is only true if you use <= or <=> implication signs. In these proofs you are tring to prove a statement, call it Z. You start from a known statement, A and follow a logical argument A => B => C => ... => Z. If you assume Z true and work backwards to A showing that Z => Y => ... => A, This is not the same as the first unless you can show that Z <=> Y <=> ... <=> A.
0
14 years ago
#26
(Original post by It'sPhil...)
This is only true if you use <= or <=> implication signs. In these proofs you are tring to prove a statement, call it Z. You start from a known statement, A and follow a logical argument A => B => C => ... => Z. If you assume Z true and work backwards to A showing that Z => Y => ... => A, This is not the same as the first unless you can show that Z <=> Y <=> ... <=> A.
i didnt work backwords though..

and also when proving a trig identity u can work both ways becouse it is tautologous???
0
14 years ago
#27
(Original post by lgs98jonee)
i didnt work backwords though..

and also when proving a trig identity u can work both ways becouse it is tautologous???
Hehe ok, but identities are differne since LHS = RHS is one statement, you could assume it is true and show that (LHS = RHS) => ... => (1 = 1) or (0 = 0) or anything like that. This is invalid as a proof, however (0 = 0) => ... => (LHS = RHS) is ok. But the standard is to show that RHS = ... = LHS or vice versa
0
X
new posts

Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• University of the Arts London
MA Performance Design and Practice Open Day Postgraduate
Thu, 24 Jan '19
• Brunel University London
Sat, 26 Jan '19
• SOAS University of London
Sat, 26 Jan '19

### Poll

Join the discussion

#### Are you chained to your phone?

Yes (57)
19.32%
Yes, but I'm trying to cut back (119)
40.34%
Nope, not that interesting (119)
40.34%